2017
DOI: 10.1016/j.diii.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of emergency transarterial embolization in acute lower gastrointestinal bleeding: A single-center experience

Abstract: TAE is a safe and effective treatment to control massive acute LGIB, especially in the emergency setting with a clinical success rate of 63%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…All of them were performed by the same experienced interventional radiologist (GRR). Reasons for unsuccessful transcatheter arterial embolization in this setting may include both technical failures and the development of complications such as bowel ischaemia [68]. The main cause for technical failure of transcatheter arterial embolization described in the literature is the inability to perform superselective catheterization of the bleeding vessels; in our series, technical success was accomplished in all three cases, as demonstrated by complete occlusion of the bleeding vessels confirmed by a control radiographic series.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…All of them were performed by the same experienced interventional radiologist (GRR). Reasons for unsuccessful transcatheter arterial embolization in this setting may include both technical failures and the development of complications such as bowel ischaemia [68]. The main cause for technical failure of transcatheter arterial embolization described in the literature is the inability to perform superselective catheterization of the bleeding vessels; in our series, technical success was accomplished in all three cases, as demonstrated by complete occlusion of the bleeding vessels confirmed by a control radiographic series.…”
Section: Discussionsupporting
confidence: 52%
“…The main cause for technical failure of transcatheter arterial embolization described in the literature is the inability to perform superselective catheterization of the bleeding vessels; in our series, technical success was accomplished in all three cases, as demonstrated by complete occlusion of the bleeding vessels confirmed by a control radiographic series. On the other hand, it is known that superselective embolization reduces the frequency of secondary colonic ischaemia to less than 13% [68], and none of our patients developed this complication. Clinical or anatomical factors related to rebleeding after colonic arterial embolization have not been clearly established, although the underlying diagnosis seems to be relevant.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…They treated by endoscopic clips and histoacryl glue injection instead of colectomy. It has been reported that colonic perforation due to ischemia after embolization could occur [ 17 ]. In the present case, ischemia due to embolization in addition to inflammation due to severe pancreatitis may have caused perforation of the colon near the splenic flexure.…”
Section: Discussionmentioning
confidence: 99%